Plant Signal Transduction - Scheel, Dierk; Ed (Oxford University Press, 2002)
Plant growth and development is controlled by environmental cues (e.g. light, salinity) that are sensed by the plant via a variety of signal transduction pathways. This book gives an up-to-date summary of the large amount of information that is now available on the processes involved in the communication of plants with their environment